Phenotypes of Cornelia de Lange syndrome caused by non-cohesion genes: Novel variants and literature review - Shangguan, Huakun; Chen, Ruimin (Frontiers in Pediatrics, 2022)
Background: Cornelia de Lange syndrome (CdLS) is a genetic disorder caused by variants in cohesion genes including NIPBL, SMC1A, SMC3, RAD21 and HDAC8. According to the 2018 consensus statement, a patient with clinical scored ≥11 points could be diagnosed as CdLS. However, some variants in non-cohesion genes rather than cohesion genes can manifest as phenotypes of CdLS. Objectives: This study describes 6 variants of non-cohesion genes (KDM6A, KMT2D, KMT2A ANKRD11 and UBE2A), and assesses the reliability of 11-points scale criteria in the clinical diagnosis of CdLS. Methods: Whole exome sequencing (WES) was performed on 6 patients with features of CdLS. Phenotypic and genotypic spectra of 40 previously reported patients with features of CdLS caused by non-cohesion genes variants and 34 previously reported patients with NIPBL variants were summarized. Clinical score comparison among patients with NIPBL variants versus those with variants in non-cohesin genes was performed. Results: Variants in non-cohesion genes were found in 6 patients [KMT2A (n=2), KMT2D, ANKRD11, KDM6A and UBE2A]. Of them, 4 variants (KMT2A c.7789C>T, ANKRD11 c.1757_1776del, KDM6A c.655-1G>A and UBE2A c.439C>T ) were novel. Combining with previously reported cases, 46 patients with phenotypes of CdLS caused by variants in 20 non-cohesion genes are now reported. From this total cohort, the average clinical score of patients in ANKRD11 cohort, SETD5 cohort and AFF4 cohort was statistically lower than those in NIPBL cohort (8.92±1.77 vs 12.23±2.58, 7.33±2.52 vs 12.23±2.58, 5.33±1.53 vs 12.23±2.58; p<0.05). The average clinical score of KMT2A cohort, EP300 cohort and NIPBL cohort had not significantly different from (11±2.19 vs 12.23±2.58, 10±4.58 vs 12.23±2.58; p>0.05). Conclusion: We described 4 novel variants of non-cohesion genes in 6 Chinese patients with phenotypes of CdLS. Of note, 3 genes (KMT2D, KDM6A and UBE2A) causing features of CdLS have never been reported. The proposed clinical criteria for CdLS needed to be updated and refined, insofar as WES was necessary to confirm the diagnosis of CdLS. Our study expanded the spectra of non-cohesion genetic variations in patients with features of CdLS.